Competencias digitales y autorregulación para el aprendizaje en estudiantes universitarios - Muñoz, Celso; Huaranga, Liliana; Pari, Dina; Mamani, Manuel; Pérez, Nancy; Panduro, Otilia (2022)
This book comprises an investigation that sought to expose the central points on the relationship between digital skills and self-regulation in online learning environments. For this, a quantitative approach methodology was adopted. The study was descriptive and correlational in order to validate the central study hypothesis. A total of 411 students from the General Studies Unit of the National University of Central Peru in the city of Huancayo (Peru) participated, who, in a non-random way, responded to two question questionnaires. It was found that the majority of students of the total sample investigated present achievement of basic level digital skills. It was also established that the highest proportion of students in the total sample reflect a high level of self-regulation in online learning environments. Thus, a direct and significant high-level correlation (r = 0.60) was found between the study variables, in students of the training area of ​​architecture and engineering (r = 0.65), in students of the area of ​​administrative sciences, accounting and economics (r = 0.74), in the students of the formative area of ​​social sciences a direct, significant high-level correlation was found (r = 0.60). A direct, significant, moderate-level correlation was only found in the students of the training area of ​​agricultural sciences and campuses (r= 0.47) and in the students of the training area of ​​health sciences (r = 0.56).
Keywords: skills; information and communication technologies; self-regulation; online learning; higher education